Do Running Mates Matter? : The Influence of Vice Presidential Candidates in Presidential Elections - Devine, Christopher, 1984-; Kopko, Kyle C., 1984- (Book collections on Project MUSE., 2020)
"What difference do running mates make in a presidential election? Research shows that vice presidents matter while in office, and there has been ample evidence of their importance in recent administrations, as demonstrated by Dick Cheney, Joe Biden, and Mike Pence. But there has been no comprehensive, quantitative study of the significance of vice presidential candidates on presidential voting. In Do Running Mates Matter?, Christopher Devine and Kyle Kopko fill this gap in our understanding of presidential elections. They first analyze people's expectations of the influence that running mates have on an election before exploring in detail their actual influence. Building on their previous work in The VP Advantage, they show that voters rarely vote based on their approval or disapproval of the vice presidential candidate, but these candidates exert an indirect effect on voting by influencing voters' perceptions of the presidential candidates. Drawing on extensive empirical data, Devine and Kopko clear up illusions about the effects of running mates and remind us that presidential candidates should pick someone who can be a good vice president, not someone who they think will secure them the win"--